Analysis of traction motor axle cap repair programs using technology numerical control - Wahyu Wibowo, Ferry (International Journal of Engineering and Technology, 2018)
In the process of a product manufacturing has a significant role in low costs of the production. Due to this case, the railway workshop has employed the numerical machine to repair the train component damages. This paper aims at analyzing a repairing program of the GE 761 traction motor axle cap using a technology numerical control (TNC) 355. The TNC itself is included on a category of a numerical control which is a method in operating a manufacturing machine automatically. The numerical data are needed to provide a part that is used by the machine which is known as a part program. The part program is processed by the machine to activate the motors that run the machine. This paper has analyzed 4 programs to repair the axle cap.Â Â Â